Ancaman Keamanan Pesisir: Studi Kasus Pagar Laut di Tangerang, Indonesia Dalam United Nations Convention on the Law of the Sea (UNCLOS) - Nabila Salsabila Putri Azha Kastella; Agussalim Burhanuddin; Ahmad Rifqih Ghazali (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
As the world’s largest archipelagic state, Indonesia holds a strategic geographical position that simultaneously renders it vulnerable to multifaceted maritime security threats. One of the most pressing recent issues is the construction of a coastal barrier (pagar laut) along the Tangerang coastline in Banten Province, which has raised significant legal, social, and environmental concerns. This study examines the legality of such structures through the lens of international maritime law, particularly the United Nations Convention on the Law of the Sea (UNCLOS) 1982. Employing a normative legal approach and qualitative analysis, this research assesses both national and international legal instruments relevant to maritime space governance. The findings indicate that the unauthorized construction of the coastal barrier violates several national regulations namely, laws governing coastal management, marine utilization, and environmental protection while also infringing upon core UNCLOS principles such as the right of innocent passage, freedom of navigation, and marine environmental protection. This study underscores the urgent need for integrated national maritime governance, regulatory harmonization, and cross-sectoral coordination to ensure compliance with international legal standards and safeguard public access to marine spaces. The Tangerang coastal barrier case exemplifies the rise of non-traditional maritime security threats in Indonesia, calling for more assertive and structured legal and policy responses.